Rainfall-Groundwater Table Fluctuations Impact on Root Zone Soil Water Simulated in Upflow for Crop Production Planning in Obio Akpa Watershed, Nigeria - Ikpe Udom; Samuel Nta; Godwin Usoh; Matthew Kamai; Boniface Ugwuishiwu (Journal of Digital Food, Energy & Water Systems)
The non-predictability of rainfall-groundwater table relationships in the ungauged Obio Akpa watershed has rubbished remedial measures against seasonal crop losses.    This study utilizes ten years (2011-2020) climate data obtained from the study area to predict the seasonal rainfall-groundwater table variations and simulate the effects on crop root zone using Upflow model. Twelve wells monitored monthly, characterized the seasonal behaviour of the Groundwater Table (GT). Gravimetric direct measurements of soil water contents were the inputs to UPFLOW model used to simulate the seasonal responses of GT to rainfall. Correlation-regression analysis was used to obtain a prediction equation of GT responses to rainfall. Results showed that in the month of April, the mean rainfall of 230mm induced GT rise of 1.35m (35%) from 3.85m in March to 2.50m in April. The effect on the soil water properties included a corresponding increase of 1.8 vol.% (10.7%) in field capacity at equilibrium with the water table in the preceding month. Mean soil water condition remained optimal at 15.9 vol.% with the GT at 1.5m below the root zone. In September and October when 1859mm and 2129mm of the mean annual rainfall was received, the water table increased by 72% and 74% respectively, and field capacity in equilibrium with the GT increased to 34.9 vol.%. causing GT inundation of the root zone (RZ) and deficit aeration in 74% of the RZ respectively. In November, with reduced rainfall amount and decreased input to groundwater, only 16% of the RZ was in deficit aeration. UPFLOW simulations of the annual soil water regime showed the months of September, October and November as high GT months suitable for planting and harvesting of only shallow rooted, short maturity crops. This knowledge will guide effective water resources and crop management in the watershed.